Fast Photoelectric Conversion in the Near‐Infrared Enabled by Plasmon‐Induced Hot‐Electron Transfer. Issue 43 (8th September 2019) - Yu, Yuanfang; Sun, Yue; Hu, Zhenliang; An, Xuhong; Zhou, Dongming; Zhou, Hongzhi; Wang, Wenhui; Liu, Kaiyang; Jiang, Jie; Yang, Dandan; Zafar, Zainab; Zeng, Haibo; et al.
Abstract: Interfacial charge transfer is a fundamental and crucial process in photoelectric conversion. If charge transfer is not fast enough, carrier harvesting can compromise with competitive relaxation pathways, e.g., cooling, trapping, and recombination. Some of these processes can strongly affect the speed and efficiency of photoelectric conversion. In this work, it is elaborated that plasmon‐induced hot‐electron transfer (HET) from tungsten suboxide to graphene is a sufficiently fast process to prevent carrier cooling and trapping processes. A fast near‐infrared detector empowered by HET is demonstrated, and the response time is three orders of magnitude faster than that based on common band‐edge electron transfer. Moreover, HET can overcome the spectral limit of the bandgap of tungsten suboxide (≈2.8 eV) to extent the photoresponse to the communication band of 1550 nm (≈0.8 eV). These results indicate that plasmon‐induced HET is a new strategy for implementation of efficient and high‐speed photoelectric devices. Abstract : Interfacial charge transfer is a crucial process in photoelectric conversion. Plasmon‐induced hot‐electron transfer is demonstrated as a sufficiently fast charge‐transfer process to realize high‐speed photoelectric conversion. A near‐infrared photodetector with fast detection speed and extended spectral response to the communication band (1550 nm) is achieved built on a tungsten suboxide nanocrystal arrays–graphene heterostructure.